Reproducibility and equivalence of GDLAM protocol mobile application for the evaluation of functional autonomy - Araujo-Gomes, Rafaela C. (2020)
This study aimed to develop a mobile application (App) for the Latin American Group for the Development of the Elderly (GDLAM) protocol of functional autonomy in the Android environment and check its reproducibility. This study was divided into two stages: 1) creation and development of the GDLAM App, Android Studio software, and JAVA as a programming language; 2) evaluation of 63 volunteers for the GDLAM protocol using the traditional method and the App. The significance level was set at p<0.05. There were no statistical differences between the traditional GDLAM protocol and the App. However, the total time required to assess the GDLAM protocol using the App was significantly lower (p <0.001). In addition, the levels of agreement between assessments exhibited strong and very strong positive correlations with significance (p <0.001) for all variables. The study showed that the use of the GDLAM App is as efficient as the traditional functional autonomy protocol for the elderly, demonstrating that reproducibility is adequate, assessment time shorter, and results are obtained faster.